2022
DOI: 10.1109/tits.2021.3131793
|View full text |Cite
|
Sign up to set email alerts
|

Deviation Point Curriculum Learning for Trajectory Outlier Detection in Cooperative Intelligent Transport Systems

Abstract: Cooperative Intelligent Transport Systems (C-ITS) are emerging in the field of transportation systems, which can be used to provide safety, sustainability, efficiency, communication and cooperation between vehicles, roadside units, and traffic command centres. With improved network structure and traffic mobility, a large amount of trajectory-based data is generated. Trajectory-based knowledge graphs help to give semantic and interconnection capabilities for intelligent transport systems. Prior works consider t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…However, this work focused on fixed services and scheduling decisions made at the time of application design. The cooperative vehicle and pedestrian-enabled ITS paradigms presented in these studies [2][3][4]. These studies suggested cooperative schemes in which vehicles can offload their workload and communicate with each other to avoid any collisions with pedestrians in smart cities.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this work focused on fixed services and scheduling decisions made at the time of application design. The cooperative vehicle and pedestrian-enabled ITS paradigms presented in these studies [2][3][4]. These studies suggested cooperative schemes in which vehicles can offload their workload and communicate with each other to avoid any collisions with pedestrians in smart cities.…”
Section: Related Workmentioning
confidence: 99%
“…IoT-based applications like traffic prediction, ticketing, and trip planning are widely utilized in public transport. In European countries, it is common for trams and buses to be ridden on the road, while the metro and train are ridden on distinct routes [3,4]. As a result, public transport providers collaborate to offer user-friendly services to passengers.…”
Section: Introductionmentioning
confidence: 99%
“…(1) for all user U i in original trajectory sequence traj i (2) for all trajectory in U i (3) for all Sampling point C i in traj k (4) Record start time t si (5) Judge the area where C i is located loc i (6) if loc i ≠ loc i−1 (7) Record end time t ei (8) if…”
Section: Fst-fpm Algorithm Descriptionmentioning
confidence: 99%
“…scan fuzzy semantic trajectory database FD (4) calculate the support P of each sequence (5) calculate the fuzzy stay time membership S(Δt) of each sequence accord to the time membership function (6) if P < σ and μ A j (Δt) < ρ (7) the sequence is less than the minimum support threshold and fuzzy stay time membership threshold (8) define the sequence as an infrequent itemset and delete it (9) create a new sequence database Q i and add frequent itemsets with length i to the database (10) for each frequent itemset T in the sequence database Q i (11) construct the projection database C w of frequent itemset T (12) get the frequent itemset T k of C w (13) T and T k are constructed as frequent sequences T i with length i (14) FTFP � FTFP ∪ T i (15) if projection database C w is not empty (16) repeat steps 8-12, i � i + 1 (17) else output frequent sequence FTFP (18) end for (19) end if (20) return FTFP ALGORITHM 2: FST-FPM algorithm.…”
Section: Fst-fpm Algorithm Descriptionmentioning
confidence: 99%
See 1 more Smart Citation